Assessment of Impacts of Wastewater Discharge in River Rwizi in Mbarara City. - Niwenyesiga, Dison (Kabale University, 2024)
A series of studies were conducted to indicate the level of environmental degradation being witnessed today. Globally, aquatic ecosystems are highly polluted. Over the past decades, increased human activity near surface water sources has adversely affected the water and ecological quality. A study was done to determine the potential impact of wastewater discharges in Mbarara City (Uganda) on the surface water quality. This research focused on both point and diffuse wastewater sources of domestic and industrial origins. Water and Wastewater samples were taken from one discharge sampling point representing residential origin and that from River Rwizi. Sample analysis was mainly limited to; the 5-day Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), turbidity, color, Ph, and E. coli because of their relevance as indicators of surface water pollution. These were to be compared with standards set by NEMA for wastewater. The study identified wastewater outflows into surface water mainly carried by unlined drains. The wastewater sources included; residential homes, car washing bays, and pit latrines. Efforts should thus be directed towards best management practices for the reduction of wastewater loads in the area.